INTERLEVEL PARAMETRIZATION OF LINGUISTIC CREATIVITY - Ubaydullaeva Madina (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article analyses how the linguistic creativity is expressed on different language levels. The author carries out research on all the levels i.e. phonological, morphological, lexical, syntactical and phraseological. The task of our study is to consider various types of linguistic creativity in a literary text, based on their interlevel parametrization. Linguistic and creative manifestations can be observed in texts of various genres and styles. Then we will talk about creative text in a broad sense. However, the degree of creativity will be different in one or another text.